Toll-Like Receptors in Leishmania Infections: Guardians or Promoters? - Marilia S. Faria; Flavia C. G. Reis; Ana Paula C. A. Lima (Journal of Parasitology Research)
Protozoa of the genus Leishmania cause a wide variety of pathologies ranging from self-healing skin lesions to visceral damage, depending on the parasite species. The outcome of infection depends on the quality of the adaptive immune response, which is determined by parasite factors and the host genetic background. Innate responses, resulting in the generation of mediators with anti-leishmanial activity, contribute to parasite control and help the development of efficient adaptive responses. Among those, the potential contribution of members of the Toll-like receptors (TLRs) family in the control of Leishmania infections started to be investigated about a decade ago. Although most studies appoint a protective role for TLRs, there is growing evidence that in some cases, TLRs facilitate infection. This review highlights recent advances in TLR function during Leishmania infections and discusses their potential role in restraining parasite growth versus yielding disease.